Curative Effect of Crude Exopolysaccharides of Some Macrofungi on Alcohol-induced Liver Damage. (May 2013) - Uyanoglu, Mustafa; Yamac, Mustafa; Canbek, Mediha; Senturk, Hakan; Kartkaya, Kazım; Oglakci, Aysegul; Turgak, Ozge; Kanbak, Gungor
Abstract The authors investigate the curative effects of crude exopolysaccharides (EPS) produced by four Basidomycetes strains on the symptoms of alcoholic liver injury. EPSs were administered to experimental groups at levels of 100 mg per kg body weight per day for 7 days using an oral zonde needle after the onset of the disease. Serum levels of alanine transaminase (ALT), lactate dehydrogenase (LDH), DNA fragmentation, caspase-3 activities, and mitochondrial outer membrane integrity were determined following sacrifice of the rats. Light and transmission electron microscope (TEM) studies were performed on liver sections for histopathological and cytological evaluations. EPS that was obtained from Coprinus comatus OBCC 1014 decreased serum ALT level and increased outer membrane integrity, and allowed for the regaining of histologically and cytologically normal hepatocyte and tissue views. As a result, based on the obtained data, it can be argued that among all studied mushroom strains crude exopolysaccharides from Coprinus comatus OBCC 1014 strain have therapeutic potential for alcoholic liver injury according to control groups.